2011
DOI: 10.1189/jlb.1010577
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical role of CD16+CCR2+CCR5+ monocytes in tuberculosis: efficient APC in pleural effusion but also mark disease severity in blood

Abstract: The role of CD16(-) and CD16(+) Mo subsets in human TB remains unknown. Our aim was to characterize Mo subsets from TB patients and to assess whether the inflammatory milieu from TB pleurisy modulate their phenotype and recruitment. We found an expansion of peripheral CD16(+) Mo that correlated with disease severity and with TNF-α plasma levels. Circulating Mo from TB patients are activated, showing a higher CD14, CD16, and CD11b expression and Mtb binding than HS. Both subsets coexpressed CCR2/CCR5, showing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
78
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 41 publications
9
78
2
1
Order By: Relevance
“…Interestingly, since IL-1β has been described as an IL-12-inducing agent on human , the reduction of IL-1β + cells observed in CD16 + Mo-DCs could be associated with the low levels of IL-12 + cells. As TB patients have a high percentage of circulating CD16 + Mos [11,12], this dichotomy in the differentiation fate of Mo subsets can explain the impairment observed in Mo-derived DCs from TB patients [21]. In addition, we observed that CD16 + depletion in Mos from TB patients improved the differentiation toward DCs and that the addition of CD16 + Mos impaired the differentiation of Mos from HSs.…”
mentioning
confidence: 50%
See 4 more Smart Citations
“…Interestingly, since IL-1β has been described as an IL-12-inducing agent on human , the reduction of IL-1β + cells observed in CD16 + Mo-DCs could be associated with the low levels of IL-12 + cells. As TB patients have a high percentage of circulating CD16 + Mos [11,12], this dichotomy in the differentiation fate of Mo subsets can explain the impairment observed in Mo-derived DCs from TB patients [21]. In addition, we observed that CD16 + depletion in Mos from TB patients improved the differentiation toward DCs and that the addition of CD16 + Mos impaired the differentiation of Mos from HSs.…”
mentioning
confidence: 50%
“…It is currently accepted that different Mo subsets may reflect developmental stages with distinct physiological functions [4] and that the CD16 + Mo subset constitutes a more mature form of the CD16 − subset [49]; thereby, the higher p38 activity in CD16 + Mos may contribute to their higher activation degree. In this regard, we suggest that CD16 + Mos are less prone to differentiate to DCs as a result of their more advanced commitment for a specific function compared with CD16 − Mos accordingly to their more activated phenotype [12].The differential capacity of Mo subsets to give rise to APCs populations has been reported in mice where two major populations have been identified on the basis of Ly6C and CX3CR1 expression [50]. In particular, it is known that in lungs DCs develop from both Ly6C high and Ly6C low Mos, while M s originate from Ly6C low Mos, which resemble the human CD16 + subset [41].…”
mentioning
confidence: 98%
See 3 more Smart Citations